The Right to Prior Consultation of the Wixárika Indigenous Peoples in the Construction of the "Las Cruces" Hydroelectric Dam of the Naáyeri Community (Cora) Presidio de los Reyes, Municipality of Ruiz, Nayarit, México (Palimpsesto, 2019)
The indigenous peoples of Mexico have the fundamental right to prior, free and informed consultation before the authorities take a decision or approve a project that is intended to be executed within the indigenous territories and that affects them directly or indirectly. This right is regulated by the Political Constitution of the United Mexican States, international treaties and federal laws, in order to provide indigenous peoples with legal tools within their reach and to defend their legitimate rights that for many centuries have corresponded to them
Keywords: Indigenous Peoples; Indigenous Law; Prior; free and informed consultation